Data-Driven Strategies for Optimizing Customer Journeys Across Telecom and Healthcare Industries (International Journal of Engineering and Computer Science, 2021)
Organizations in the telecom and healthcare industries generate terabytes of data every day from a myriad of sources, including customer interactions from their web, mobile apps, and social media; marketing campaigns including customer responses; billing; customer feedback; transactional systems; prescription patterns; clinical trials; employee accounts; partner interactions; and so on. The question is how to tap into these volumes of data to glean insights that help optimize the overall business process, address customers' needs, and enhance their experience with the organization—essentially, optimize the customer journey. The customer journey is a framework used to understand how a customer interacts with an organization over time, including before becoming a customer, while purchasing a product, during its lifetime, and ending with discontinuing the relationship. This is especially critical in industries, such as telecom and healthcare, that have a longer customer lifecycle and, therefore, higher costs associated with customer acquisition, retention, and win-back. By applying analytics to customer journey data, organizations can gain a deeper understanding of pain points that arise along the journey and address them with new strategies. These strategies might modify transition points, add actions to enhance customers' experiences or reduce communication delays. Using machine learning algorithms, organizations could also create predictive models that identify customers who are more likely to churn or transition to a different buying group. Furthermore, by incorporating market data and internal associate feedback, organizations can optimize their investment in digital experience platforms, brand building, and trial marketing to improve sales closure rates.In this document, we will first provide an overview of the telecom and healthcare industries, followed by a description of the various data-driven strategies that companies can adopt to enrich and optimize customer journey experiences based on the nature of the organization and its objectives. We will provide some examples of organizations that have successfully implemented these strategies and conclude with a discussion regarding the challenges of implementing data-driven customer journey strategies in the telecom and healthcare industries.